Historiografi Islam Nusantara: Sebuah Identifikasi - Asmawati, Rika inggit; Subekti, Arif (UIN Raden Mas Said Surakarta, 2020)
Islam was, and still, one of mainstream themes of Indonesia historiography. This article aims to identify some historical studies of Islam in the Archipelago. The spirit of decolonization, the sublimation of asian values, official history projection, and or alternative historiography, are temporarily identifications among Indonesian islamic history, sublimation sublimation.